Tren dan Perkembangan dalam Penelitian tentang Motivasi Berprestasi pada Atlet Pelajar: Analisis Bibliometrik - Nur Annisa, Aghnia Nafilah; Liche Seniati, Ali Nina; Sudarwati A, Lilik (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2026)
This study examines research trends on achievement motivation among student-athletes using a bibliometric approach. Data were obtained from the Scopus database, resulting in 146 journal articles published between 1982 and 2025. The analysis covered publication trends, citation patterns, journal productivity, and keyword co-occurrence. Results show a significant increase in publications after 2010, with a peak in 2024. Citation analysis reveals that a small number of highly cited studies dominate the field, indicating concentrated academic influence. Keyword mapping identifies major themes such as achievement motivation, sport performance, and student-athletes, with emerging topics related to psychological and contextual factors. This study provides a comprehensive overview of research development and identifies gaps and future research directions in sport psychology.